The association between parental knowledge and attitudes on children's picky eating behaviour - Hasan, Haliza; Abdul Hamid, Siti Hazariah; Mohd Hambali, Siti Nor Hanis (Malaysian Nurses Association, 2023)
Background: Food is essential for human health as it provides nutrients and energy to assist growth and development. Childhood is an essential period for growth and development. Food consumption and picky eating are significant to understanding by parents to prevent malnutrition and obesity that may lead to other health conditions in future. Purpose: This study aimed to determine the parental knowledge and attitude and the association between the level of knowledge and attitudes related to children's picky eating behaviour in Kuantan, Pahang. Methodology: A cross-sectional study was conducted among 147 parents using convenience sampling. All participants who fulfilled the inclusion criteria were recruited in this study. Results: Data analysis revealed that most participants have a high level of knowledge (95.9%) and practices (94.6%) related to children's picky eating behaviours. There is a significant association between the level of Knowledge and attitude regarding children’s picky eating behaviour with an r-value of 0.708 (p-0.001). Conclusion: The study findings revealed that parents in Kuantan have a high level of